Psychiatric symptoms and insulinoma: A case report - Cristina, Colán T. (2013)
Introduction: Insulinomas are pancreatic endocrine neoplasms with a low incidence between 1-4 cases per million per year. Case description:'A female 49 years-old with neurological and psychiatric symptoms were treated for two years as a psychiatric patient. Presented a glucose value, which reflects hypoglycemia. The patient was operated with resolution of symptoms. Conclusion: Assess all patients with psychiatric symptoms and perform a complete medical history and laboratory findings, being the most opportune glucose.